BUSINESS PLAN PREPARATION STRATEGY FOR STARTING A NEW BUSINESS: LITERATURE REVIEW - Dini Salamah; Sarah sitynuraeny; Monica Tsani Octavia; Wiranta (International Journal of Multidisciplinary Reseach, 2026)
A business plan is a strategic document that helps business founders translate business ideas into operational, marketing, funding, and performance control directions. This article aims to analyze business plan development strategies for starting a new business through a literature review. The study results indicate that an effective business plan must be developed in stages, starting with problem and market validation, competitor analysis, selecting an appropriate plan format, developing a marketing strategy and revenue model, creating realistic financial projections, and adjusting to legal structures and funding needs. The literature also shows that business plans tend to have a positive impact on new venture development, but the benefits are strongest when planning is combined with market learning and ongoing revision, rather than treated as a rigid document (Delmar & Shane, 2003; Brinckmann, Grichnik, & Kapsa, 2010). Thus, a good business plan serves not only as an administrative requirement, but as a living, adaptive , and data -driven decision-making tool.